Prognostic impact of melphalan dose and total body irradiation use in patients with acute myeloid leukemia undergoing allogeneic stem cell transplantation with reduced-intensity conditioning. Issue 6 (12th May 2019) - Harada, Kaito; Yanada, Masamitsu; Machida, Shinichiro; Kanamori, Heiwa; Onizuka, Makoto; Ozawa, Yukiyasu; Kobayashi, Hikaru; Sawa, Masashi; Katayama, Yuta; Ohashi, Kazuteru; Kanda, Junya; Ichinohe, Tatsuo; et al.
Abstract: To evaluate the prognostic impact of melphalan dose and total body irradiation (TBI) use in acute myeloid leukemia patients undergoing reduced-intensity allogeneic transplantation, we retrospectively compared outcomes of patients receiving a higher-dose (120–140 mg/m 2, n = 379) or lower-dose melphalan (80–110 mg/m 2, n = 128) with or without TBI of ≤4 Gy. At 3 years, overall survival was 48.9% in the higher-dose group versus 40.3% in the lower-dose group ( p = .013). This survival benefit was attributed to lower tumor-related mortality (23.9% vs. 31.7%; p = .049). Non-relapse mortality did not differ (24.8% vs. 23.5%, p = .59). The beneficial effect of a higher-dose melphalan was more evident when combined with TBI in younger patients, those not in complete remission, and those with good performance status. Our findings support the use of a higher-dose melphalan in combination with TBI for reduced-intensity conditioning in physically fit patients.